Rapid progression of an IDH-wild type histological low-grade glioma harbouring TERT promoter mutation and diffuse CD34 expression: a case report - Wang, Hongxiang; Tan, Cong; Xu, Tao; Li, Weiqing (Folia Neuropathologica, 2021)
IDH-wild type (WT) histological low-grade gliomas are a rare group with distinct character and prognostic heterogeneity. Studies involving genetic and molecular analyses are warranted to stratify these patients into specific entities for the facilitation of tumour management. In this study, we reported a novel IDH-WT glioma with histological characteristics of a low-grade tumour. Preoperative CT revealed massive calcification of this lesion and MRI showed a mixed hyperintense and hypointense signals on both T1- and T2-weighted images with a slight contrast enhancement. Micrography revealed dense deposits of calcium and diffuse microhaemorrhage in the tumour mass. Immunohistochemical staining showed diffuse expression of CD34 in neoplastic cells but uncertain positivity of glial fibrillary acidic protein (GFAP). Further sequencing found telomerase reverse transcriptase (TERT) promoter mutation in this tumour. Though the patient underwent surgical treatment followed by radiotherapy and temozolomide chemotherapy, the tumour recurred at the eight-month follow-up postoperatively. Taken together, extensive CD34 expression and TERT promoter mutation may empower the potential of malignant transformation to IDH-WT histological low-grade glioma to rapidly progress into glioblastoma.